MODAL SOSIAL PADA SANGGAR BINA TASIK DI KECAMATAN PANGKALAN KERINCI KABUPATEN PELALAWAN - Sari, Nesi Novita; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at Sanggar Bina Tasik, Pangkalan Kerinci District, Pelalawan Regency. The background of raising this research is because Sanggar Bina Tasik is an art community that exists in Pangkalan Kerinci, has been established for 10 years and has participated in national and international events. The researcher is interested in seeing the relevance of this with social capital consisting of trusts, networks and norms. This thesis aims to describe the social capital in the Bina Tasik studio, and to find out the elements of social capital in maintaining the existence of the Bina Tasik studio. This research is a qualitative research with a descriptive approach. The data used in the form of primary and secondary data, as well as data collection techniques carried out by the method of observation, interviews, and documentation of all things that answer the problems regarding social capital research in the Bina Tasik studio. The informants of this study consisted of members and parties who had a cooperative relationship with the Bina Tasik studio. Based on the results of the research, social capital plays a role in maintaining the compactness of members of the Bina Tasik Studio, maintaining Existence, building Networks, and improving the quality of the Bina Tasik Studio. The existence of elements of social capital (trusts, networks and norms) makes the Bina Tasik studio capable of binding its members to a compactness, so that this community is able to maintain and maintain its existence. The element of social capital that has the most role in the development process of the Tasikmalaya studio is the element of trust.Keywords: Social Capital, Trust, Network, Norm